2024
DOI: 10.1093/jncics/pkae012
|View full text |Cite
|
Sign up to set email alerts
|

Opioid use in cancer patients compared with noncancer pain patients in a veteran population

Seshadri C Mudumbai,
Han He,
Ji-Qing Chen
et al.

Abstract: Background Opioid safety initiatives may secondarily impact opioid prescribing and pain outcomes for cancer care. Methods We reviewed electronic health record data at a tertiary Veterans Affairs system (VA Palo Alto) for all patients from 2015-2021. We collected outpatient Schedule II opioid prescriptions data and calculated morphine milligram equivalents (MMEs) using CDC conversion formulas. To determine the clinical impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Moderate-to-severe pain, which can be considered an indication for opioid prescription, was reported by 38% of all patients. Expectedly, a large study conducted on the veteran population found that cancer patients were almost twice as likely to have an opioid prescription compared with noncancer patients [ 82 ]. These numbers raise a concern regarding the risk of developing opioid use disorders such as dependency or misuse among cancer patients and survivors [ 83 , 84 ].…”
Section: Prescription Opioids In Patients With Cancermentioning
confidence: 99%
“…Moderate-to-severe pain, which can be considered an indication for opioid prescription, was reported by 38% of all patients. Expectedly, a large study conducted on the veteran population found that cancer patients were almost twice as likely to have an opioid prescription compared with noncancer patients [ 82 ]. These numbers raise a concern regarding the risk of developing opioid use disorders such as dependency or misuse among cancer patients and survivors [ 83 , 84 ].…”
Section: Prescription Opioids In Patients With Cancermentioning
confidence: 99%